دراسة تحليلية للنهج البيئي للتسويق السياحي - بكار, موساوي; عبد الباسط, كرباع; عبد الكريم, نصرات (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الدراسة إلى تحليل النهج البيئي للتسويق السياحي الذي يتعلق بالمسؤولية الاجتماعية والمسؤولية الاجتماعية البيئية، محاولين بذلك الاجابة عن الاشكالية الرئيسية المتمثلة في " ما مدى تأثير النهج البيئي في التسويق السياحي؟، وقد استعنا في هذه الدراسة بالمنهج الوصفي في الجانب النظري منها، والاستبيان في الجانب التطبيقي الذي سيعالج من خلال تطبيق معطيات برنامج ال spss، على عدد من المؤسسات السياحية المختلفة مستخدمين في \لك عينة مكونة من 46 عاملا به\ه المؤسسات ليتم التوصل إلى نتائج مختلفة من أهمها أن المؤسسات الجزائرية السياحية تعتمد على كل من المزيج التسويقي السياحي، كما أنها تحافظ على المكونات البيئية متحملة ب\لك المسؤولية الاجتماعية البيئية تجاه البيئة. This study aims to analyze the environmental approach to tourism marketing that relates to social and environmental social responsibility, attempting to answer the main problem of “what is the impact of the environmental approach on tourism marketing?” In this study, we used the descriptive approach in the theoretical aspect, and the questionnaire in The practical aspect that will be addressed through the application of the data of the spss program, on a number of different tourist establishments using in \ you a sample of 46 workers in \ e establishments to reach different results, the most important of which is that the Algerian tourist enterprises depend on each of the tourism marketing mix, It also preserves the environmental components, bearing the social and environmental responsibility towards the environment.
Keywords: المسؤولية الاجتماعية، المسؤولية الاجتماعية البيئية، النهج البيئي، التسويق السياحي.; social responsibility, environmental social responsibility, environmental approach, tourism marketing.